FORTEPIANO MUZÍKALÍQ SHÍǴARMALARÍNDA KÓRKEM OBRAZLARDÍ JARATÍW - Abdullaeva, U. (SCIENCE and SOCIETY, 2023)
In this article, it is said that before the teacher can explain and show the studied works to the student through specific examples, he must have a wide and diverse knowledge. Learning to play a musical instrument is a creative activity even in children's lives. It is not only a special scientific activity, but it also requires activity, goal-seeking, attention and discipline.